The Influence of Perceived Ease of Use and Perceived Enjoyment on Repurchase Intention Through Customer Trust - Mahjudin Mahjudin; Muhammad Yusuf Aria Widjaja; Rachel Yusriyah Bilqis Mahjudin (Journal of Managerial Sciences and Studies, 2026)
The rapid growth of e-commerce has intensified competition among digital platforms, making customer retention a critical determinant of business sustainability. In this context, understanding the factors that encourage consumers to make repeat purchases has become increasingly important. This study aims to examine the effects of perceived ease of use and perceived enjoyment on repurchase intention, both directly and indirectly through customer trust as a mediating variable. The study adopts a quantitative approach using a descriptive and causal research design. Data were collected through questionnaires distributed to users of Swee Lee e-commerce in Greater Jakarta. A total of 240 respondents were selected using a purposive sampling technique. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that perceived ease of use has a positive and significant effect on repurchase intention and customer trust. Similarly, perceived enjoyment has a positive and significant effect on both repurchase intention and customer trust. Furthermore, customer trust is found to have a positive and significant influence on repurchase intention. The mediation analysis reveals that customer trust significantly mediates the relationship between perceived ease of use and repurchase intention, as well as the relationship between perceived enjoyment and repurchase intention. These findings suggest that consumers are more likely to engage in repeat purchasing behavior when they perceive an e-commerce platform as easy to use, enjoyable, and trustworthy. The study contributes to the growing body of literature on consumer behavior in e-commerce by extending the Technology Acceptance Model (TAM) through the inclusion of customer trust as a mediating mechanism. From a managerial perspective, the findings highlight the importance of improving platform usability, enhancing user experience, and strengthening consumer trust to foster long-term customer loyalty and sustainable business performance in the digital marketplace.